Spin Vortex Resonance in Non-planar Ferromagnetic Dots - Ding, Junjia (Sci Rep, 2016)
In planar structures, the vortex resonance frequency changes little as a function of an in-plane magnetic field as long as the vortex state persists. Altering the topography of the element leads to a vastly different dynamic response that arises due to the local vortex core confinement effect. In this work, we studied the magnetic excitations in non-planar ferromagnetic dots using a broadband microwave spectroscopy technique. Two distinct regimes of vortex gyration were detected depending on the vortex core position. The experimental results are in qualitative agreement with micromagnetic simulations.